Morphological and Cultural Linguistic Approaches on Lexicon ‘Mama’ in the Dengka Dialect - Dian Rahmani Putri; Efron Erwin Yohanis Loe (Soshum: Jurnal Sosial dan Humaniora, 2026)
Dengka dialect is spoken in Rote Northwest District, Rote Ndao Regency, East Nusa Tenggara Province. Dengka is one of eighteen Rote dialects. This study focuses on the Dengka dialect spoken by the Oetutulu villagers. The goal of the research is to document the Dengka dialect while also learning about the speaker's culture. The study questions concern the use of the lexicon 'mama' based on morphology and cultural linguistics. In the Rote Dengka Society, the verb 'mama' is exclusively used to describe the subject's behaviour, which is to chew sirih-pinang, a herbal chew made from areca nut, betel, lime, and tobacco. The use of morphology and cultural-linguistics theoretical approaches is designed to get the best possible results in analysis. The research method includes careful observation and interaction with each technique. The descriptive qualitative technique is used to describe all data. Data collected from an informant in Oetutulu Village with certain requirements. The findings of this study reveal that the lexicon 'mama' can be used in morphology in several ways, including: a) as a free morpheme, b) by affixation, and c) through full and partial reduplication. Meanwhile, in cultural linguistics, the researcher discovered nine domains which apply the lexicon 'mama': a) marriage domain, b) death domain, c) family domain, d) mutual assistance domain, e) government domain, f) togetherness domain, g) reconciliation domain, h) social domain, and i) figurative language domain. The result of this research is that to make a culture documnentation that related to ‘mama culture’ (budaya makan sirih) as an inheritance cultural for the youth generation at Dengka society and for the readers, also for the next researchers to make a research that has the same topics in another culture.